Prevalência, extensão e gravidade de lesões de furca em uma amostra rural do sul do Brasil - Tatsch, Karen Finger (2020)
The objective of this cross-sectional study is to estimate the prevalence, extent and severity of furcation involvement (FI) in a representative sample of a rural area in southern Brazil. The total sample comprised 688 individuals (≥15 years), in this study 494 individuals were analyzed who presented at least one 1st and/or 2nd molar. Complete periodontal clinical examinations were performed at six sites of all teeth except for the third molars. Sociodemographic, economic and behavioral questionnaires were applied. Degree of FI (I, II and III) was assessed in all molar furcation entrances and prevalence was determined at three levels of analysis (individual, molar and furcation entrance). Prevalence for individual and molar level were estimated considering at least one tooth or entrance with FI. The prevalence of furcation entrances was determined independently. The FI extent was assessed only for individuals and molars with involvement. As the main results, the prevalence of FI per individual was 59.7% with an extent of 47% of molars and 25,5% of furcation entrances. The FI prevalence increased with age and was higher in the maxilla than in the mandible (33,1% and 19,1%, respectively). The distal entrance was the most involved (25.7%) and teeth 17 and 26 presented the highest prevalence at the molar and or furcation entrance levels. Severity per entrances was 16,3% for the degree I, 5,1% for degree II and 1.1 for III. It is possible to conclude that a high prevalence, extent and severity of FI was observed clinically, highlighting the importance of to include the furcation exam in routine dental appointments.